Cocaine self-administration differentially activates microglia in the mouse brain. (29th May 2020) - Burkovetskaya, Maria E.; Small, Robert; Guo, Liyang; Buch, Shilpa; Guo, Ming-Lei
Highlights: We established cocaine self-administered mice. We observed microglial activation the brain striatum. Cocaine differentially modulates microglial functional status in vivo . NLRP3/IL1β may play critical roles in cocaine-mediated microglial activation. Abstract: The evidence showing the involvement of microglial activation in the development of drug addiction remain scarce as microglia have not been systematically investigated in self-administered mice, a gold standard rodent model for drug addiction. Here we established the stable cocaine self-administration mice to examine microglial activation levels in various brain regions related to reward circuitry. Immunostaining for Iba1 showed a significant upregulation of intensity in the striatum but not in the medial prefrontal cortex (mPFc), hippocampus or thalamus. Further validation experiments showed that cocaine self-administered mice had significantly increased mRNA expression of ccl2 and IL1β in the striatum but not the mPFc compared to saline controls. Consistently, we found elevated protein levels of Iba1, CCL2, TLR4 and mature IL1β in the striatum, not in the mPFc of cocaine-receiving mice. In addition, cocaine-stimulated microglia had modified morphology including a reduced number of intersections, a shortened length and number of processes in the NAc. In summary, our results demonstrated that cocaine mediated microglial activation in a region-specific manner in vivo . These findings indicate that microglia could be activated in the early stage of cocaine addiction directly supporting the rationale that dysregulation on neuroimmune signaling is inherently involved in the development of drug addiction.